Framing the constructive alignment of design within technology subjects in general education - Buckley, Jeffrey; Seery, Niall; Gumaelius, Lena; Canty, Donal; Doyle, Andrew; Pears, Arnold (International journal of technology and design education, 2021)
Design is core element of general technology education internationally. While there is a degree of contention with regards to its treatment, there is general consensus that the inclusion of design in some form is important, if not characteristic, of the subject area. Acknowledging that design is important, there are many questions which need to be considered in order to guide policy and practice, such as whether a singular general design ability can be explicitly defined empirically beyond an implicit verbal definition, and whether it can be taught and assessed. In order to address these questions in a systematic fashion, a framework is needed in order to guide relevant investigations. Having such a framework would allow for theory to be generated, hypotheses to be tested, and assumptions to be challenged. In response to this apparent need, this article presents a theoretical discussion pertaining to the constructive alignment of learning to design, wherein theories of knowledge, variation theory, knowledge transfer, and assessment validity and reliability are reflected upon.